Implementation of the Child-Friendly Regency Program in Fulfilling Children's Rights in Belitung Regency - Eliza, Vira; Nainggolan, Atirista; Suradi, Suradi (Jurnal Ilmiah Perlindungan & Pemberdayaan Sosial,, 2024)
The implementation of the Child-Friendly District (KLA) Program is a strategic initiative by the government to ensure the fulfillment of children's rights in a safe and supportive environment. Belitung District, despite achieving the Madya level KLA status in 2023, still faces several issues related to violations of children's rights. This study aims to provide an in-depth overview of the implementation of the KLA Program in Belitung District, focusing on the aspects of communication, resources, disposition, and bureaucratic structure.The study employs a qualitative approach with a descriptive design. Purposive sampling techniques were used to select informants, including technical program implementers from district to village levels and relevant program beneficiaries. Data were collected through in-depth interviews, observations, document studies, and focus group discussions (FGDs).The results of the study indicate that the communication aspect is still suboptimal, particularly in the socialization of the program to implementers at sub-district and village levels. The resource aspect also requires improvement, as there are still implementers who lack understanding of KLA indicators, shortages of facilities and infrastructure, limited coordination among implementers, and insufficient program funding. The bureaucratic structure aspect reveals that the Standard Operating Procedures (SOP) for program implementation are not yet fully understood by all implementers. Based on these findings, this study proposes a program called "Capacity Building for KLA Program Implementers Through Time to Sharing for KLA" to address the identified challenges.